Sustainable Business Ethics Based On The Triple Bottom Line In Scrap Metal Trading: A Case Study Of Cv Logam Jaya, Sumenep - Asror Karomah; Rizki Febri Eka Pradani (International Journal of Management and Business Economics, 2026)
This study examines the implementation of sustainable business ethics based on the Triple Bottom Line in the scrap metal trading business at CV Logam Jaya, Sumenep, Madura. The scrap metal sector contributes to local economic activity and metal waste recycling, yet it faces ethical challenges related to material sourcing, price transparency, occupational safety, and environmental responsibility. Using a qualitative field research approach, data were collected through observation, in-depth interviews, and documentation involving the owner, employees, suppliers, customers, and local community members. Data were analysed through data reduction, data presentation, and conclusion drawing, with validity ensured through triangulation. The findings show that sustainable business ethics are reflected in honest and transparent transactions, concern for employee and community welfare, responsible resource management, and efforts to reduce social and environmental risks. The implementation is supported by the owner’s moral awareness, customer trust, strong social relations, business experience, and long-term sustainability orientation. However, it is hindered by economic pressure, limited understanding of sustainable ethics, weak regulatory supervision, and unhealthy market competition. This study contributes to the understanding of how Triple Bottom Line-based ethics can strengthen stakeholder trust and support business sustainability in the informal scrap metal trading sector.